An extrauterine extensively metastatic epithelioid trophoblastic tumor responsive to pembrolizumab - Sarah G. Bell; Shitanshu Uppal; Michelle D. Sakala; Andrew P. Sciallis; Aimee Rolston (Elsevier, 2021)
We report a case of extrauterine epithelioid trophoblastic tumor (ETT)-the rarest variant of gestational trophoblastic tumor-that has been stable on nearly two years of pembrolizumab treatment. A 47-year-old gravida 2, para 2 who underwent a prophylactic bilateral salpingo-oophorectomy nine years prior and bilateral mastectomy five years prior in the setting of a strong family history of breast and ovarian cancer with no genetic testing performed, presented to an outside clinic with recurrent respiratory infections without resolution despite antibiotics. Radiology and pathology testing confirmed the ETT diagnosis, including a second opinion from the John I. Brewer Trophoblastic Disease Center of Northwestern University's Feinberg School of Medicine, and the patient was started on a chemotherapy regimen of etoposide, methotrexate, actinomycin-D, etoposide, and cisplatin for seven cycles, with partial improvement in her disease. After PD-L1 testing showed the tumor had > 5% PD-L1 positivity, she initiated pembrolizumab in April 2019. CT imaging after three months revealed decreased lung, abdominal, and pelvic disease and she was continued on pembrolizumab. As of December 2020, she had completed 29 cycles of pembrolizumab, with a plan for her to continue treatment indefinitely given her decreased, but persistent, disease. Our findings suggest pembrolizumab is a reasonable option for treatment of patients with significant PD-L1 positivity on testing of the tumor.